Variación del fonema /s/ en posición implosiva en el español hablado en el cantón Loja - Mora Alberca, Isaac Joel (2022)
The voiceless alveolar fricative phoneme is one of the most studied in the Spanish language (López Morales, 1993; Moreno Fernández, 1997 and Tejalda Giráldez, 2012). Its variability is due to linguistic (Samper Padilla, 1992), social (Lipski, 1986) and situational factors (Hualde, 2014). In this research, the reductionism of the sound in implosive position is specifically addressed, and the general objective is to analyze the dull alveolar fricative phoneme in Loja. The eight informants were selected from the corpus currently being elaborated by a research team attached to the National University of Loja and whose collection began in August 2019 from unstructured interviews in order to get the vernacular 13 language and overcome the paradox of the observer (Labov, 1983). The eight informants are equally distributed distinguishing sex (male and female) and ages representing four generations (G1: 18-40; G2: 40-60; G3:60-80; and G4: 90+). It conforms to qualitative design, as sociolinguistic phenomena are described and explained, but the analysis relies on quantitative operations. Praat software is used as a tool of acoustic phonetics to more precisely identify the phenomenon. The results indicate that the varvariant of the phoneme /s/ that predominates in all informants, without distinction of social or linguistic variables, is [s], which had a total of 99% of realizations.